Efektivitas Strategi Penilaian dalam Pembelajaran Berdiferensiasi untuk Menilai Keragaman Potensi Siswa: Studi Literatur Sistematis - Sri Sumarni; Indah Permata Sari; Ahmad Nurul Azhar Al Adhim; Dimas Triananda Aji Pamungkas; Subekti; Dwi Haryanti (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
Assessment in differentiated instruction presents challenges for educators due to the diversity of students' potentials. This study reviews the effectiveness of assessment strategies in differentiated instruction to evaluate the diversity of student potentials. The method used is a Systematic Literature Review of 15 relevant articles published between 2020 and 2025. The findings indicate that diagnostic, formative, and summative assessments, as well as adaptive and multiformat assessments, are effective in accommodating diverse learning needs. Identified challenges include time constraints, lack of teacher training, and technological barriers. Adjusting assessment strategies through flexible methods, the use of portfolios, tiered tasks, and the integration of technology is key to enhancing the effectiveness of assessment in differentiated instruction. These findings provide important recommendations for educators in designing more inclusive and responsive assessments to accommodate student diversity.